Dynamics of applied phosphorus and transformations between different forms of phosphorus in some Syrian soils: Study of soil –P fractionation - Alloush, Ghiath; Hatta, Osama (Latakia University Journal -Biological Sciences Series, 2018)
A pot experiment was conducted in a greenhouse at Tishreen University location. The experiment included three soils differ in their chemical properties: 1) heavy clay red soil rich in iron oxides; 2) a silt loam basiltic soil rich in manganese oxides; 3) clay red soil rich in calcium carbonate (34.8 %). Treatments included application of different levels of triple super phosphate (TSP, 46 % P2O5) ranged from 0, 20, 40, 60, 80, to 100, mg P/kg soil were added to 0.5 kg soil. Pots were randomized in a green house, watered regularly to maintained 75% of the water holding capacity. Sub-samples were taken from each pot at times (0-30-60-90-120-150-180-210-240 Day). Soil P fractionation was only preformed for samples withdrawn at times 0 and 240 days.أسفل النموذج The incubation of the native soils led to an increase in available P in all soils after 240 day of incubation. The increase in extracted soil Pi differed mainly in ‏phosphorus extracted with‏ ‏‎0.5M ‏NaOH‎‏ and‏‏ ‏‎1M HCl‎‏. This may be due to variation in soil properties and the range of TSP that was applied. Most of added phosphorus was presence in red and basiltic soils were extracted in 0.5M NaOH. In red calcareous soil, added P was mainly fixed starting from the application rate of 60 mg P/kg. Fixed P in calcareous soil constituted 14.5% at the rate of 60 mg P/kg soil, and increased to reach 25.4% at the rate of 100 mgP/kg. These rates of P-fixation with Ca are higher than those fixed with oxides and hydroxides Fe-P and Al-P. There was a decline in the residual organic phosphorus forms in all soils and at all different rates of TSP application. This was probably due to the transformation of residual-Po into other forms of organic or inorganic P forms that are more available for plant uptake. حركية الفوسفور المضاف وتحولاته بين الأشكال المختلفة للفوسفور في بعض الترب السورية: دراسة تجزئة الفوسفور في التربة أجريت تجربة تحضين في البيت البلاستيكي في موقع مشتل جامعة تشرين، استخدم في الدراسة ثلاثة ترب مختلفة في خواصها الفيزيائية والكيميائية تم جمعها من مناطق مختلفة في سوريا: 1- تربة حمراء طينية ثقيلة تتميز بمحتواها العالي من الأكاسيد، 2- تربة بازلتية سلتية لومية، 3- تربة حمراء طينية تتميز بمحتواها العالي من كربونات الكالسيوم (34.8%). تضمنت التجربة تسميد فوسفاتي باستخدام سوبر فوسفات مركز (TSP) تركيز 46% P2O5 بمعدلات متدرجة (0-20-40-60-80 و100مغP/كغ تربة) وإضافتها إلى 0.5 كغ تربة. وزعت الأصص عشوائياً على مربع التجربة مع المحافظة على 75% من سعة حمولة التربة للماء, أخذت عينات من كل أصيص في الأزمنة (0-30-60-90-120-150-180-210-240 يوم)، وأجريت تحاليل تجزئة الفوسفور للزمنين 0 و 240 يوم. ارتفعت قيم الفوسفور المتاح بشقيه العضوي والمعدني في معاملة الشاهد لجميع الترب المدروسة بعد 240 يوم من التحضين، اختلفت الزيادة في الأشكال اللاعضوية للفوسفور المستخلصة بـ 0.5 M من NaOH و 1 M من HCl، وذلك بحسب خواص كل تربة ومستويات الإضافة من الـ TSP. لقد تواجد الجزء الأكبر من الفوسفور المضاف الذي تعرض للتثبيت في التربتين الحمراء والبازلتية في مستخلص NaOH. لقد بدأ تثبيت الفوسفور المضاف في التربة الحمراء الكلسية بدءاً من معدل الإضافة 60 مغP/كغ حيث تكون نسبة الفوسفور المثبتة من المضاف 14.5%، وتزداد لتصبح 25.4% عند معدل الإضافة 100 مغP/كغ، مع تفوق الجزء المرتبط بالكالسيوم Ca-P مقارنة بما تم تثبيته حديثاً على سطوح الأكاسيد والهيدروكسيداتFe-P ، Al-P. لقد انخفض الشكل العضوي للفوسفور المتبقي في معادن التربة Residual-Po في جميع الترب المدروسة وعلى اختلاف مستويات التسميد حيث تحولت لأشكال أخرى معدنية أو عضوية أكثر إتاحة.